Pancasila sebagai Landasan Etis dalam Penegakan Hukum terhadap Tindak Pidana Terorisme - Ahmad Muhamad Musain Nasoha; Ashfiya Nur Atqiya; Tresa Anasti; Dita Ayu Rahmadhani; Shofi Hana Hanifah (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The application of Pancasila as an ethical foundation in law enforcement against criminal acts of terrorism in Indonesia highlights the importance of integrating humanitarian values and human rights principles. This article analyses how Pancasila, with its focus on social justice and humane treatment, distinguishes Indonesia's approach from repressive methods commonly applied in other countries. The research method used in this article is a descriptive qualitative approach, which includes document analysis as well as in-depth interviews with various stakeholders, including law enforcement, academics, and deradicalisation practitioners. The data obtained is analysed to evaluate the effectiveness of deradicalisation programmes based on the principles of Pancasila and its impact on reducing radicalisation as well as reintegration of former terrorism perpetrators. By emphasising the need for a balanced policy between security and human rights, the Pancasila-based approach proved to be more effective and sustainable in the long run. Challenges in the consistent application of Pancasila values are faced in the context of globalisation and advances in information technology. The results show that this approach not only reduces radicalisation but also facilitates the reintegration of former terrorism perpetrators into society. In conclusion, the application of Pancasila in law enforcement contributes significantly to national stability and can be a model for other countries in countering global terrorism.